2020
DOI: 10.29252/mlj.14.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antifungal Effect of Fluconazole Combined with ZnO Nanoparticles against Candida albicans Strains from Vaginal Candidiasis

Abstract: Background and Objective: The prevalence of the infections caused by Candida species has led to a significant increase in their resistance to antifungal compounds. The aim of this study was to i) investigate drug resistance ii) evaluate the incidence of Candida albicans drug resistance pattern in the vaginal samples of women referring to health centers of Qom province, and iii) examine the effect of Zn nanoparticles combined with fluconazole against C. albicans isolates. Methods: This experimental, descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Zinc oxide nanoparticles are considered the most promising of these for drug release and low toxicity [ 141 , 142 , 143 ]. As with silver nanoparticles, zinc nanoparticles show significant anti-candida effects both as a monotherapy [ 144 , 145 ] and in combination with antifungal drugs such as fluconazole [ 146 ]. Thus far, the in vitro antifungal activities of zinc nanoparticles have been evaluated with various strains of C. albicans, C. krusei, C. aprapsilosis, and C. tropicalis [ 116 , 144 , 147 ].…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%
“…Zinc oxide nanoparticles are considered the most promising of these for drug release and low toxicity [ 141 , 142 , 143 ]. As with silver nanoparticles, zinc nanoparticles show significant anti-candida effects both as a monotherapy [ 144 , 145 ] and in combination with antifungal drugs such as fluconazole [ 146 ]. Thus far, the in vitro antifungal activities of zinc nanoparticles have been evaluated with various strains of C. albicans, C. krusei, C. aprapsilosis, and C. tropicalis [ 116 , 144 , 147 ].…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%
“…Second is the release of zinc ions in medium with effects on active transport as well as on the amino acid metabolism [ 129 ]. Hajar et al [ 130 ] showed the synergistic effect of ZnONPs with fluconazole against C. albicans, and Xue et al [ 131 ] demonstrated the synergistic inhibition of Phytophthora growth by 0.25 g/L ZnONPs with 0.01 g/L thiram.…”
Section: Biomedical Applications and Mechanism Of Action Of Zinc Oxid...mentioning
confidence: 99%
“…Recently synthesized nanostructures of zinc, manganese, and thioacetamide have been found to possess antifungal activity against pathogenic fungal species [42]. In recent studies, ZnO nanoparticles were synthesized that exhibited antifungal activity [43][44][45][46][47]. In low concentrations, silver nanoparticles were less cytotoxic than zinc oxide nanoparticles and represent an alternative antimicrobial compound against A. hydrophila, A. salmonicida and A. invadans [48].…”
Section: Zinc Nanostructures and Their Hybridsmentioning
confidence: 99%